Constitutional Court's Limitation on the Resubmission Ofindictments - Ahmad Syahird; Rahmad Masturi; Muhammad Kamran (LEGAL BRIEF, 2024)
This study aims to determine the legal consequences of limiting the resubmission of indictments by the constitutional court and the legal certainty of limiting the resubmission of indictments by the constitutional court. This type of research is normative with data collection techniques carried out through library research, namely laws and regulations, a case approach, namely the Constitutional Court Decision, and a conceptual approach. In addition, the author also conducts library research through data and books related to the research topic. Furthermore, the data obtained was analyzed qualitatively which was then presented descriptively. The results of the study show that: 1) The legal consequences of limiting the re-submission of indictments that have been canceled make the decision in the form of a final decision because it has been examined and considered the subject matter of the case and will be nebis in idem if filed again afterwards. The form of legal action that can be taken by the public prosecutor is an appeal or cassation and not resistance (verzet). In order to harmonize this form of legal action with the Constitutional Court's decision, additional arrangements are needed which contain new norms in criminal procedural law; and 2) The Constitutional Court's decision which limits the re-submission of indictments is a form of legal certainty. Thus, in order to prevent repeated cancellation of the indictment, the prosecutor's accuracy is required in preparing the indictment because at the second examination, there is a potential for the indictment to still not meet the material requirements so that the case is considered finished without any examination of the main case, and there is a potential for an indictment still does not meet the material requirements, while the subject matter of the case is proven. This resulted in no settlement and clarity of the status of the case for the accused and victims to obtain a guarantee of fair legal certainty as mandated in Article 28D paragraph (1) of the 1945 Constitution